One Numerical Complex Analysis Method for Parameters Identification of Piecewise Homogeneous Conductivity Media with Using Applied Quasipotential Tomographic Data - Bomba, A.Ya.; Boichura, M.V. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2016)
We propose one approach for gradient problems solving of parameters identification in piecewise homogeneous fields based on numerical complex analysis method with using applied quasipotential tomographic data. На основі числових методів комплексного аналізу запропоновано підхід до розв’язання градієнтних задач ідентифікації параметрів кусково-однорідних середовищ за даними томографії прикладених квазіпотенціалів.